(untitled) (Archives of Criminology, 1996)
The treatment of alcoholism poses exceptionally numerous problems; what is more, it is but seldom that the traditional treatment of alcohol dependent persons (alocoholics) proves successful. The activity of Alcoholics Anonymous provides sufficient proof that the use of religious faith in the treatment of alcoholics may yield desirable results. Faith is to help alcoholics towards spiritual revival and formition of a new personality enabling them to abstain. The research project aimed at verifying a general hypothesis that religiousness may be one of catalysts of abstention during disaccustoming treatment. We sought to answer the question about the impact of religious faith on the examined alcoholics’ attitude to drinking. Thus religiousness was treated in our statistical analyses as one of the factors that condition the alcohol-related behaviour of persons in the course of disaccustoming treatment. Empirical research was conducted in the years 1984-1985 in Lower Silesia and involved four populations. The study bases on a representative sample of 322 persons treated in outpatient disaccustoming clinics (Ao) and 135 patients of hospital disaccustoming wards (Aн). Aiming to “reproduce” the social environment of alcoholics, we selected control groups (Ko) and (Kн) to match the former two populations. Each member of the control soup matched a member of the population of alcoholics in respect of the following socio-demographic traits: sex, age, marital status, place of residence, level of education, occupation and source of maintenance. Thus the above socio-demographic traits were distributed identically in the populations of alcoholics and their corresponding control groups (A=K). Not at all trivial is the role in this process of environmental factors. Alcohol consumption is not distributed evenly throughout society, the bulk of alcoholic beverages being consumed by a small proportion of Polish people. The high degree of concentration of vodka consumption indicates the existence of sociaf environments which are much more alcoholism-prone than the rest of society. For this reason, in the research project we focused on reconstruction of the characteristics of the social environments that "supply" outpatient clinics and hospitals with alcoholics. The drinking habits in the two examined populations (Aօ and Aн) differ. The differences concern both the frequency of drinking and the amount of alcohol consumed on one occasion. Some of those differences should be stressed here: porsons treated in outpatient clinics tend to drink strong alcoholic beverages more often but exercise some restraint as regards the amount consumed on one occasion. The hospital patients, instead, tend rather to get drunk whenever drinking but drink less often. Due to this difference, the risk of becoming an alcoholic is bigger in the environment that “supplies” patients to hospitals as compared to that of persons treated in outpatient clinics. Members of the population of hospital patients were somewhat younger. Frequent excessive drinking results in a high degree intoxication that speeds up the development of alcoholism in young patients. What has also to be stressed is the fact that the alcoholics’ social backgrounds differ in many other respects as well. Among hospital patients, as opposed to persons treated in outpatient clinics, there is a bigger proportion of men; they are younger (as has been mentioned above) but also polarized to a greater extent as regards age; more of them live in villages and small towns; they have no family of their own (either they have not yet established one or the family they established has already disintegrated); they have no children; they earn a lot but have no flat of their own; they are ernployed as qualified manual workers; some find it difficult to stay on a regular job. Coincidence of the above environmental conditions increases the risk of alcohol dependence. Comparison of the hospital patients’ environment with that of persons treated in outpatient clinics offers many indications that the situation of the latter can be seen as generally more advantageous. They are somewhat older (a larger proportion of them representing the middle age categories); they have families (a lower proportion being divorced), and frequently also children; and most are permanently employed. It was revealed by the project that among hospital patients, there was a larger proportion of persons from extreme sections of distribution of socio-demographic traits while most persons treated in outpatient clinics show normal distributions of those variables. It can thus be concluded that there is among the latter a much bigger proportion of persons in a generally stable life situation. Important here is their undisturbed matrimonial life and permanent employment, as the family and workmates make it possible to control the negative effects of drinking. Just as important is the fact that the compared social environments of alcoholics (Ao and Aн) are unlike each other regarding their degree of involvement in religious practices. Persons treated in outpatient clinics show consistent attitudes towards faith; this is evidenced by a distinct polarization into those who regularly participate in religious practices and persons who never go to the church at all. Among hospital patients, instead, there is a much bigger proportion of persons who are irresolute as to their own faith and take part in religious life but occasionally. Alcoholism may lead to a lowered degree of religiousness and, as a result, to a considerable decrease in, and sometimes total desistance from participation in many religious practices. The project sought to answer questions such as e.g.: What is the degree of religiousness of examined alcoholics? Is their religiousness different from that of non-alcoholic population? If so, to what extent? General religious declarations of persons treated in outpatient clinics are similar as regards their attitudes towards faith. Instead, such persons more often declare lack of religion or religious indifference which may indicate a growing polarization of attitudes (religiousness or lack of religion). Alcoholism contributes to neglect in religious duties. Persons treated in outpatient clinics attend the Sunday service less regularly than other men from a similar social enviroment. Also, fewer alcoholics go to church on Easter: a smaller proportion (as compared to that found in a similar environment) observe the Easter duty and receive the Holy Communion. The high degree of religious declarations typical of the soclal background of hospital patients is somewhat lower in the case of alcoholics themselves. The drop is distinct, instead, as regards participation in religious practices of hospital-treated alcoholics. They attend the Sunday service but occasionally, and more often fail to go to church on Easter. On the other hand, their motivation seems stronger regarding the Easter duty. The period of hospital treatment and advanced alcoholism disturb the rhythm of periodical religious practices. We analyzed the correlation between religiousness (participation in the basic religious practices) and drinking habits. Religiousness was found to stimulate a limitation of both the frequency of drinking and the amount consumed on one occasion in men from the group of persons treated in outpatient clinics (Kօ, Ao). Regular participation in religious life through performance of the obligatory practices coincides with sobriety in everyday life. Instead, religious irresolution consisting in neglect of the Sunday and Easter practices is accompanied by a radical deterioration in the sphere of drinking habits. What seems particularly important from the viewpoint of the problems under analysis is the fact that participation in religious practices (on Sundays and Easter alike) reduces the frequency of drinking in persons treated in outpatient clinics. A drop in the amount of vodka consumed by those persons on one occasion is related mainly to the Easter practice. On the other hand, the study failed to confirm good effects of religiousness on the drinking habits in the environment of hospital patients (Kн, Aн). Hospital patients are no doubt alienated from their social background to a greater extent than persons treated in outpatient clinics. This is evidenced by their late start of the disaccustoming treatment. Over 60% of hospital patients live in small and medium-sized towns as well as villages while persons treated in outpatient clinics are chiefly inhabitants of big cities (58%) and medium-sized towns (41%). This indicates weakness of disaccustoming clinics in small localities, due to their small number, understaffing, and the locals’ unawareness of alcoholism being a disease.